An application of the Toronto Childhood Cancer Stage Guidelines in three population‐based cancer registries: The case of central nervous tumors. Issue 6 (17th April 2020) - Sacerdote, Carlotta; Mosso, Maria Luisa; Alessi, Daniela; Merletti, Franco; Tagliabue, Giovanna; D'Agostino, Anna; Fabiano, Sabrina; Savoia, Fabio; Piga, Patrizia; Sessa, Marcella; Vetrano, Francesco; Gatta, Gemma; et al.
Abstract: Background: Cancer stage is a determinant of survival of childhood central nervous system (CNS) cancers and could help the interpretation of survival variability among countries. Consensus guidelines to stage childhood malignancies in population cancer registries ("Toronto Childhood Cancer Stage Guidelines") have been recently proposed with the goal of data comparability. Indeed, stage is not systematically recorded in all registries and, when it is, different classification systems are used. We applied the Toronto Childhood Cancer Stage Guidelines to CNS cancer cases of three population‐based cancer registries with the aim of evaluating the feasibility of staging this type of cancer and the critical points in the classification of CNS tumors. Procedures: The Toronto Childhood Cancer Stage Guidelines were applied to 175 CNS patients, diagnosed from January 1, 2002 to December 31, 2014 in three cancer registries in Italy, and the percentage of cases that could be staged was assessed. Results: One hundred eight of 126 (86%) medulloblastomas and other embryonal CNS cancers and 22 of 49 (45%) ependymomas were staged. Using these guidelines, survival of children with localized tumors could be discriminated from that of children with metastatic disease. Conclusions: The use of the Toronto Childhood Cancer Stage Guidelines is feasible for staging medulloblastoma in Italian population‐based cancer registries, whereas it is more difficult for ependymomas. In Italy, cerebrospinal fluid examination, one of the decisive tests to stage CNS tumors, is not routinely performed as a first‐line diagnosis procedure in ependymoma pediatric patients. A similar exercise by a larger number of cancer registries in different countries could suggest improvements in the childhood cancer staging system.